Roles of GTP and Rho GTPases in pancreatic islet beta cell function and dysfunction. (2nd November 2021) - Kowluru, Anjaneyulu
ABSTRACT: A growing body of evidence implicates requisite roles for GTP and its binding proteins (Rho GTPases) in the cascade of events leading to physiological insulin secretion from the islet beta cell. Interestingly, chronic exposure of these cells to hyperglycaemic conditions appears to result in sustained activation of specific Rho GTPases (e.g. Rac1) leading to significant alterations in cellular functions including defects in mitochondrial function and nuclear collapse culminating in beta cell demise. One of the objectives of this review is to highlight our current understanding of the regulatory roles of GTP and Rho GTPases in normal islet function (e.g. proliferation and insulin secretion) as well potential defects in these signalling molecules and metabolic pathways that could contribute islet beta cell dysfunction and loss of functional beta cell mass leading to the onset of diabetes. Potential knowledge gaps in this field and possible avenues for future research are also highlighted. Abbreviations: ARNO: ADP-ribosylation factor nucleotide binding site opener; CML: carboxyl methylation; Epac: exchange protein directly activated by cAMP; ER stress: endoplasmic reticulum stress; FTase: farnesyltransferase; GAP: GTPase activating protein; GDI: GDP dissociation inhibitor; GEF: guanine nucleotide exchange factor; GGTase: geranylgeranyltransferase; GGpp: geranylgeranylpyrophosphate; GGPPS: geranylgeranyl pyrophosphate synthase; GSIS: glucose-stimulated insulin secretion; HGPRTase: hypoxanthine-guanine phosphoribosyltransferase; IMPDH: inosine monophosphate dehydrogenase; α-KIC: α-ketoisocaproic acid; MPA: mycophenolic acid; MVA: mevalonic acid; NDPK: nucleoside diphosphate kinase; NMPK: nucleoside monophosphate kinase; Nox2: phagocyte-like NADPH oxidase; PAK-I: p21-activated kinase-I; β-PIX: β-Pak-interacting exchange factor; PRMT: protein arginine methyltransferase; Rac1: ras-related C3 botulinum toxin substrate 1; Tiam1: T-cell lymphoma invasion and metastasis-inducing protein 1; Trx-1: thioredoxin-1; Vav2: vav guanine nucleotide exchange factor 2